2021
DOI: 10.1177/23259671211008810
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Injuries and Pitching Performance Between Major League Baseball and Nippon Professional Baseball: A 2-Team Comparison Between 2015 to 2019

Abstract: Background: There has been minimal research investigating injury and pitching performance differences between Major League Baseball (MLB) and other professional leagues. Purpose/Hypothesis: This 2-team comparison between MLB and Japan’s Nippon Professional Baseball (NPB) involved affiliated players over 5 years. We hypothesized that teams would differ in the injury incidence, mechanism of injury, pitch velocity, and pitch type usage. Study Design: Descriptive epidemiology study. Methods: Between 2015 and 2019,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…A study comparing pitching performance in official games and the incidence of injury between an MLB team and a team in Japan's professional baseball league reported that the MLB-affiliated pitchers threw faster than their Japanese counterparts and the MLB team had a higher rate of throwing-related injuries compared with the Japanese team. 3 A similar observation of faster ball velocities in American pitchers was reported at the collegiate level. 30 This study also reported that American pitchers had greater maximal shoulder external rotation with greater peak joint torques at the elbow and shoulder than the Japanese counterparts, suggesting a possible link among kinematic characteristics, ball velocity, and risk of elbow injury.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A study comparing pitching performance in official games and the incidence of injury between an MLB team and a team in Japan's professional baseball league reported that the MLB-affiliated pitchers threw faster than their Japanese counterparts and the MLB team had a higher rate of throwing-related injuries compared with the Japanese team. 3 A similar observation of faster ball velocities in American pitchers was reported at the collegiate level. 30 This study also reported that American pitchers had greater maximal shoulder external rotation with greater peak joint torques at the elbow and shoulder than the Japanese counterparts, suggesting a possible link among kinematic characteristics, ball velocity, and risk of elbow injury.…”
Section: Discussionsupporting
confidence: 66%
“…The first is that the data were collected from Japanese pitchers only; thus, generalization of the results may require some caution in translation to other competitive populations. A study comparing pitching performance in official games and the incidence of injury between an MLB team and a team in Japan's professional baseball league reported that the MLB‐affiliated pitchers threw faster than their Japanese counterparts and the MLB team had a higher rate of throwing‐related injuries compared with the Japanese team 3 . A similar observation of faster ball velocities in American pitchers was reported at the collegiate level 30 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In fact, previous research has shown a greater injury risk in larger professional pitchers, who throw at higher velocities. 4 Future research on the relationship between body size and ligament strength would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In hitting, research has shown advancement of bat speed with improvement in lean body mass; however, such lean body mass gains were associated to improvement in vertical jump power, torso rotational strength, squat, and bench press strength profiles in highschool baseball players, thus substantiating the effect of strength training on offensive characteristics (17,18). As it relates to baseball pitching, increased body mass seems to influence throwing velocity at different stages of development and between professional pitching cohorts (6,16). A deeper investigation into lean body mass development seemed to be a strong covariant associated with absolute vertical jump power and linear and transverse momentum in the pitching delivery, all of which demonstrated to be greater in collegiate pitchers who threw at faster velocities (16).…”
Section: Introductionmentioning
confidence: 99%